Inferior ST-elevation myocardial infarction managed with a pharmacoinvasive strategy and conservative management of delayed atrioventricular block: classical case report. Issue 6 (7th December 2020) - John, Thadathilankal-Jess; Kyriakakis, Charles; Zachariah, Don; Doubell, Anton
Abstract: Background: The 2017 ESC guideline on patients with ST-segment elevation myocardial infarction (STEMI) provides guidance regarding the optimal management of these patients. Transient atrioventricular (AV) block is a relatively common complication of inferior STEMI and its management is also addressed in the guidelines. Case summary: A 64-year-old gentleman with multiple cardiovascular risk factors presented to the emergency department with a history of ischaemic type chest pain and evidence of inferior ST-segment elevation on his electrocardiogram (ECG). First-degree AV block was noted on his initial ECG. He was given thrombolytic therapy as part of a pharmacoinvasive strategy of reperfusion. He, however, failed fibrinolytic therapy, and emergency angiography revealed critical disease of the right coronary artery which was successfully stented. Subsequent to reperfusion, he developed complete AV block without evidence of re-infarction, which was managed conservatively with successful resolution of the block after 7 days of expectant management with temporary transvenous pacing. Discussion: We highlight some of the important management principles from the ESC guideline of STEMI including timing and the management of AV block in these patients. In addition, we highlight the role of a pharmacoinvasive strategy for reperfusion where timeous primary percutaneous coronary intervention cannot be performed. The usefulness of such a strategy within the COVID-19 era is also emphasized.